Pengukuran Komponen Fisik Atlet PON Cabang Olahraga Dayung Sulawesi Selatan - Andi Ihsan; Hasbi Asyhari; Sufitriono; Ilham Kamaruddin (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Based on the results of observations and monitoring carried out during the exercise of the physical condition of the rowing athletes, there are still many who do not properly follow the instructions and directions from the trainer how to do quality physical condition exercises in accordance with the components and principles of the exercise. This partnership program provides solutions on how to carry out good and correct tests and measurements of the main physical components in rowing, an explanation of how to implement a physical condition training program using weight training. Tests and measurements of the physical components carried out on rowing athletes in this partnership program are: (1) Arm muscle endurance using the push up method, abdominal muscle endurance using the sit up method and leg muscle endurance using the half squat jump method (2) Flexibility using the flexometer method (3) Eye and hand coordination by throwing the ball against the wall (4) Arm power using the medicine ball method and (5) General endurance using the bleep test method (multi stage fitness test). The results of the tests and measurements found that there were no athletes who entered the perfect category, only 1 person (6.25%) was in the Very Good category, as many as 9 people (56.25%) were in the Good category, 6 people (37.50%) were in the Enough category and none were into the Less category. The conclusion is that the physical components of the South Sulawesi rowing athletes who are prepared to take part in the XX National Sports Week in Papua are still in the Good category.